Urgensi Pembaharuan Undang-Undang Nomor 5 Tahun 1960 tentang Peraturan Dasar Pokok-Pokok Agraria - Nicholas Billy Trisno; Habib Adjie (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research is to determine the urgency of updating and Unification of Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations. The type of research method used is a normative juridical method using literature study of legal materials. Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations is a legal product that has regulated land law since 1960. This law is still in effect today. By looking at the year the legal product was created, it becomes an interesting topic regarding its validity and application. There are several problems that arise because there has been no update to the law governing land. This is due to Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations. Therefore, reform and unification of laws related to land in Indonesia are needed Keywords: Land, Land Conflict, Reform, Legal Unification